Effect of macromolecular entanglement on the simple shear flow of viscoelastic fluid - Kuznetsova, Yulia Leonidovna; Skul’skiy, Oleg Ivanovich (Computational Continuum Mechanics, 2013)
We investigate the stationary shear flow of an incompressible fluid described by the non-linear differential-vector model proposed by Remmelgassom, Harrison and Lill (RHL-model). In the absence of macromolecular entanglements, analytical expressions for orientation tensor components and material functions are derived, and the effect of the parameters of the model on their form is studied. The ranges of model parameters, in which the examined relations show ambiguity, are determined. The influence of macromolecular length limitation on the form of tensor components and material functions is studied numerically.
Keywords: viscoelastic fluid; simple shear flow; influence of macromolecular entanglements